Peter Hynes - Hynes, Peter (Irish Journal of Arts Management and Cultural Policy, 2015)
Peter Hynes, chief executive of an Irish local authority, described how local government was now much more about collaborative service delivery, place making and community development, projects in which the arts were seen as playing a central role. It’s great to be here. A previous speaker spoke about being intimidated by the quality of speakers, well you should stand here as a former County Manager – we’ve been rebranded since the beginning of the month – it’s our first public address as the newly branded ‘Chief Executive’ of Mayo County Council.